Animated Edge Textures in Node-Link Diagrams: A Design Space and Initial Evaluation - Romat, Hugo; Appert, Caroline; Bach, Benjamin; Henry Riche, Nathalie; Pietriga, Emmanuel (Proceedings of ACM SIGCHI 2018, 2018)
Animated edge textures can encode data in node-link diagrams by making sequences of small glyphs (i.e., particles) dynamically move along edges. Our framework, Flownet, supports the creation of such animated edge textures by considering an edge as a tunnel, and a node as an emitter that can fire a specific pattern of particles at a given frequency through this tunnel. Once fired, particles have their own speed, which can change. The combination of motion variables (pattern, frequency and speed) with more usual visual variables (such as color, shape, opacity), which can be applied to either particles or to the tunnel itself, opens a large design space to encode various edge attributes. Flownet also enables the definition of gates, which are invisible constructs placed along a link, that alter the properties of particles that pass through them.